10.1001/TESTjama.2012.4607 (CrossRef Listing of Deleted DOIs, 2000)
Adolescent depression and anxiety are common and impairing conditions. Scalable, engaging digital interventions offer a low-burden strategy to support youth mental health. To evaluate the association of a codesigned digital behavioral health game for adolescents with depressive and anxiety symptoms during 12 months of follow-up and to explore the association with psychosocial outcomes. This prespecified secondary analysis of a randomized clinical trial included assessments from baseline through 12 months. Eligible adolescents from 15 school-based health programs in Connecticut were 16 to 19 years of age and reported past 30-day use of alcohol, cannabis, vaping, or other nonopioid substances or elevated depression and/or anxiety symptoms. Participants were enrolled between October 21, 2021, and February 27, 2024; data analyses were completed on November 12, 2025. Participants were randomized 1:1 to a digital game of approximately 300 minutes delivered during 6 weeks or to an attention-matched active control. Prespecified secondary outcomes included depressive (8-item Patient Health Questionnaire [PHQ-8]) and anxiety (7-item Generalized Anxiety Disorder [GAD-7]) symptoms. Psychosocial outcomes included beliefs about psychological services (BAPS), help-seeking intentions, and emotion regulation. Linear mixed models with participant-level random intercepts tested group, time, and group-by-time effects. Moderation by baseline characteristics and exploratory mediation of PHQ-8 scores via BAPS were examined. Among 532 participants, 269 were randomized to the intervention and 263 to the control condition; 284 (53.4%) were male, with a mean (SD) age of 16.6 (0.7) years. A group-by-time interaction was observed for PHQ-8 scores (F3,1308 = 2.93; P = .03). At 12 months, adjusted mean PHQ-8 scores were 5.30 (95% CI, 4.74-5.86) in the intervention group and 6.42 (95% CI, 5.86-6.98) in the control group (adjusted difference, -1.12 [95% CI, -1.85 to -0.38] points), with no association detected for GAD-7. At 6 weeks, intervention participants reported higher BAPS scores (adjusted difference, 0.03 [95% CI, 0.01-0.05]). Exploratory mediation showed that early BAPS improvements were associated with PHQ-8 score reductions at 6 months. No associations with remaining outcomes or moderation were observed. In this prespecified secondary analysis of a randomized clinical trial, the intervention was associated with modest, sustained reductions in depressive symptoms during 12 months of follow-up. Early improvements in BAPS showed associations consistent with mediation of short-term depressive symptom reductions. Digital games may support adolescent mental health at scale. ClinicalTrials.gov Identifier: NCT04941950.